THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT THE MAKASSAR CITY EDUCATION OFFICE - Hilda Fatika Sari; Siti Haerani; Hasmawati Hasmawati (Jurnal Mahasiswa Manajemen, 2026)
The purpose Of thi s study is to analyze the influence of the Work Environment on employee performance through Job Satisfaction at the Makassarnis Education Office. This research was conducted at the Makassar City Education Office offic e with 55 respondents. The data analysis used was qualitative data descri ptively to explain the characteristics of the respondents and the description of the research variables. Furthermore, quantitative data is analyzed with a path analysis tool through the Statistical Package For Social Science (S PSS) program to find out information about the direct and indirect influenc e of the Work Environment on employee performance through Job Satisfa ction at the Makassar City Education Office office. The results of this study show that (1) partially the variable of the Work Environment has a positive and significant effect on job satisfaction, (2) partially the Work Environme nt has a positive and significant effect on employee performance, (3) parti ally Job Satisfaction has a positive and significant effect on employee perf ormance (4) the Work Environment has a positive and significant effect on employee performance through employee job satisfaction at the Makassar City Education Office. Based on the results of this study, it shows that to improve the performance of employees of the Makassar City Education Offi ce, it is very necessary to pay attention to the condition of the Work Enviro nment and Job Satisfaction of employees.